2013
DOI: 10.4236/jep.2013.46063
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of 2,6-Dichlorophenol Wastewater in Soil Column Reactor in the Presence of Pineapple Peels-Derived Activated Carbon, Palm Kernel Oil and Inorganic Fertilizer

Abstract: In this study, the potential effects of palm kernel oil (PKO), pineapple peels derived-activated carbon (PPAC) and NPK fertilizer (20:10:10) as amendment agents on the natural bioattenuation of 2,6-dichlorophenol (2,6-DCP) in tropical agricultural soil were investigated. The effect of PPAC dosage on 2,6-DCP biodegradation was also studied. Column reactors containing soil were spiked with 2,6-dichlorophenol (2,6-DCP) wastewater (300 mg/l) and amended with PKO, NPK fertilizer and PPAC alone or in combinations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…First, it could be hypothesized that carbonaceous amendments directly affected the growth of the TBBPA-degrading taxa (i.e., the positive responders) by providing them with a source of nutrients and readily usable carbon for their growth, as suggested by Agarry et al (2013). In addition, BC and AC could also have been used as a physical support for the formation of a TBBPA-degrading microbial biofilm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it could be hypothesized that carbonaceous amendments directly affected the growth of the TBBPA-degrading taxa (i.e., the positive responders) by providing them with a source of nutrients and readily usable carbon for their growth, as suggested by Agarry et al (2013). In addition, BC and AC could also have been used as a physical support for the formation of a TBBPA-degrading microbial biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…However, conversely because of their extraordinary sorption capabilities, there is a concern that organic compounds strongly adsorbed onto BC and AC surfaces will no longer be bioavailable for microbial degradation. Although carbonaceous amendments have been shown to slow down the biodegradation of some herbicides (Muter et al, 2014), and even prevent BDE-47 degradation by a degrading strain of Pseudomonas putida (Xin et al, 2014), most studies have reported an increase in the biodegradability of a wide range of organic pollutants in the presence of BC and AC, including, pentachlorophenol (Tong et al, 2014; Yu et al, 2015), azo dyes (Van Der Zee et al, 2003), phenanthrene (Leglize et al, 2008), 2,6-Dichlorophenol (Agarry et al, 2013), and polychlorinated biphenyls (Kjellerup et al, 2014). These findings suggest that combining both carbonaceous amendment materials and microbial degradation could be a promising strategy to improve the removal of a wide range of contaminants from wastewater and sludge.…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation of petroleum oil is described by first-order kinetics [5] , [24] and the values were calculated using Eq. (2): where C is the concentration of hydrocarbon (g/kg) at a certain time, C 0 is the initial concentration of hydrocarbon (g/kg), k is the rate constant of the change in the oil content (day −1 ) and t is the study period (day).…”
Section: Methodsmentioning
confidence: 99%
“…For CAC-soil amended microcosms; the THDB count increased 6 CFU/g; 36 to 58×10 6 CFU/g; and 38 to 64×10 6 CFU/g for 0.48 mm, 0.07 mm and 0.02 mm particle size of supplemented CAC, respectively (Figure 3a) while it increased from 26 to 46×10 6 CFU/g; 32 to 52×10 6 CFU/g; and 34 to 57×10 6 CFU/g for 20 g, 30 g and 40 g of supplemented CAC, respectively (Figure 3b). Thus, higher microbial counts were observed for microcosms with relatively smaller particle size of CAC as well as soil microcosm with higher dosage of CAC.…”
Section: Microbial Growthmentioning
confidence: 98%